(2E)‐3‐(6‐Methoxynaphthalen‐2‐yl)‐1‐(pyridin‐3‐yl)prop‐2‐en‐1‐one and its cyclocondensation product with guanidine, (4RS)‐2‐amino‐4‐(6‐methoxynaphthalen‐2‐yl)‐6‐(pyridin‐3‐yl)‐3, 4‐dihydropyrimidine monohydrate: two types of hydrogen‐bonded sheet. Issue 11 (3rd October 2014) - Nayak, Prakash S.; Narayana, Badiadka; Yathirajan, Hemmige S.; Hosten, Eric C.; Betz, Richard; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The structures of a chalcone and of its cyclocondensation product with guanidine are reported. In (2E)‐3‐(6‐methoxynaphthalen‐2‐yl)‐1‐(pyridin‐3‐yl)prop‐2‐en‐1‐one, C19H15NO2, (I), the planes of the pyridine and naphthalene units make dihedral angles with that of the central spacer unit of 23.61 (13) and 23.57 (15)°, respectively, and a dihedral angle of 47.24 (9)° with each other. The molecules of (I) are linked into sheets by a combination of C—H...O and C—H...π(arene) hydrogen bonds. In the cyclocondensation product (4RS)‐2‐amino‐4‐(6‐methoxynaphthalen‐2‐yl)‐6‐(pyridin‐3‐yl)‐3, 4‐dihydropyrimidine monohydrate, C20H18N4O·H2O, (II), the dihydropyrimidine ring adopts a conformation best described as a shallow boat. The molecular components are linked by two N—H...O hydrogen bonds, two O—H...N hydrogen bonds and one N—H...N hydrogen bond to form complex sheets, with the methoxynaphthalene interdigitated between inversion‐related pairs of sheets.